Indicators for Monitoring Undergraduate STEM Education - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Science, technology, engineering and mathematics (STEM) professionals generate a stream of scientific discoveries and technological innovations that fuel job creation and national economic growth. Ensuring a robust supply of these professionals is critical for sustaining growth and creating jobs growth at a time of intense global competition. Undergraduate STEM education prepares the STEM professionals of today and those of tomorrow, while also helping all students develop knowledge and skills they can draw on in a variety of occupations and as individual citizens. However, many capable students intending to major in STEM later switch to another field or drop out of higher education altogether, partly because of documented weaknesses in STEM teaching, learning and student supports. Improving undergraduate STEM education to address these weaknesses is a national imperative. Many initiatives are now underway to improve the quality of undergraduate STEM teaching and learning. Some focus on the national level, others involve multi-institution collaborations, and others take place on individual campuses. At present, however, policymakers and the public do not know whether these various initiatives are accomplishing their goals and leading to nationwide improvement in undergraduate STEM education. Indicators for Monitoring Undergraduate STEM Education outlines a framework and a set of indicators that document the status and quality of undergraduate STEM education at the national level over multiple years. It also indicates areas where additional research is needed in order to develop appropriate measures. This publication will be valuable to government agencies that make investments in higher education, institutions of higher education, private funders of higher education programs, and industry stakeholders. It will also be of interest to researchers who study higher education.

Improving Measurement of Productivity in Higher Education - National Research Council (The National Academies Press, 2012)
Higher education is a linchpin of the American economy and society: teaching and research at colleges and universities contribute significantly to the nation's economic activity, both directly and through their impact on future growth; federal and state governments support teaching and research with billions of taxpayers' dollars; and individuals, communities, and the nation gain from the learning and innovation that occur in higher education. In the current environment of increasing tuition and shrinking public funds, a sense of urgency has emerged to better track the performance of colleges and universities in the hope that their costs can be contained without compromising quality or accessibility. Improving Measurement of Productivity in Higher Education presents an analytically well-defined concept of productivity in higher education and recommends empirically valid and operationally practical guidelines for measuring it. In addition to its obvious policy and research value, improved measures of productivity may generate insights that potentially lead to enhanced departmental, institutional, or system educational processes. Improving Measurement of Productivity in Higher Education constructs valid productivity measures to supplement the body of information used to guide resource allocation decisions at the system, state, and national levels and to assist policymakers who must assess investments in higher education against other compelling demands on scarce resources. By portraying the productive process in detail, this report will allow stakeholders to better understand the complexities of–and potential approaches to–measuring institution, system and national-level performance in higher education.

The Integration of the Humanities and Arts with Sciences, Engineering, and Medicine in Higher Education: Branches from the Same Tree - National Academies of Sciences, Engineering,; Medicine
In the United States, broad study in an array of different disciplines 2014arts, humanities, science, mathematics, engineering2014 as well as an in-depth study within a special area of interest, have been defining characteristics of a higher education. But over time, in-depth study in a major discipline has come to dominate the curricula at many institutions. This evolution of the curriculum has been driven, in part, by increasing specialization in the academic disciplines. There is little doubt that disciplinary specialization has helped produce many of the achievement of the past century. Researchers in all academic disciplines have been able to delve more deeply into their areas of expertise, grappling with ever more specialized and fundamental problems. Yet today, many leaders, scholars, parents, and students are asking whether higher education has moved too far from its integrative tradition towards an approach heavily rooted in disciplinary \

Expanding Underrepresented Minority Participation: America's Science and Technology Talent at the Crossroads - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2011)
In order for the United States to maintain the global leadership and competitiveness in science and technology that are critical to achieving national goals, we must invest in research, encourage innovation, and grow a strong and talented science and technology workforce. Expanding Underrepresented Minority Participation explores the role of diversity in the science, technology, engineering and mathematics (STEM) workforce and its value in keeping America innovative and competitive. According to the book, the U.S. labor market is projected to grow faster in science and engineering than in any other sector in the coming years, making minority participation in STEM education at all levels a national priority. Expanding Underrepresented Minority Participation analyzes the rate of change and the challenges the nation currently faces in developing a strong and diverse workforce. Although minorities are the fastest growing segment of the population, they are underrepresented in the fields of science and engineering. Historically, there has been a strong connection between increasing educational attainment in the United States and the growth in and global leadership of the economy. Expanding Underrepresented Minority Participation suggests that the federal government, industry, and post-secondary institutions work collaboratively with K-12 schools and school systems to increase minority access to and demand for post-secondary STEM education and technical training. The book also identifies best practices and offers a comprehensive road map for increasing involvement of underrepresented minorities and improving the quality of their education. It offers recommendations that focus on academic and social support, institutional roles, teacher preparation, affordability and program development.

Minority Serving Institutions: America's Underutilized Resource for Strengthening the STEM Workforce - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
There are over 20 million young people of color in the United States whose representation in STEM education pathways and in the STEM workforce is still far below their numbers in the general population. Their participation could help re-establish the United States' preeminence in STEM innovation and productivity, while also increasing the number of well-educated STEM workers. There are nearly 700 minority-serving institutions (MSIs) that provide pathways to STEM educational success and workforce readiness for millions of students of color2014and do so in a mission-driven and intentional manner. They vary substantially in their origins, missions, student demographics, and levels of institutional selectivity. But in general, their service to the nation provides a gateway to higher education and the workforce, particularly for underrepresented students of color and those from low-income and first-generation to college backgrounds. The challenge for the nation is how to capitalize on the unique strengths and attributes of these institutions and to equip them with the resources, exceptional faculty talent, and vital infrastructure needed to educate and train an increasingly critical portion of current and future generations of scientists, engineers, and health professionals. Minority Serving Institutions examines the nation's MSIs and identifies promising programs and effective strategies that have the highest potential return on investment for the nation by increasing the quantity and quality MSI STEM graduates. This study also provides critical information and perspective about the importance of MSIs to other stakeholders in the nation's system of higher education and the organizations that support them.

Research Universities and the Future of America: Ten Breakthrough Actions Vital to Our Nation's Prosperity and Security - National Research Council (The National Academies Press, 2012)
Research Universities and the Future of America presents critically important strategies for ensuring that our nation's research universities contribute strongly to America's prosperity, security, and national goals. Widely considered the best in the world, our nation's research universities today confront significant financial pressures, important advances in technology, a changing demographic landscape, and increased international competition. This report provides a course of action for ensuring our universities continue to produce the knowledge, ideas, and talent the United States needs to be a global leader in the 21st century. Research Universities and the Future of America focuses on strengthening and expanding the partnership among universities and government, business, and philanthropy that has been central to American prosperity and security. The report focuses on the top 10 actions that Congress, the federal government, state governments, research universities, and others could take to strengthen the research and education missions of our research universities, their relationships with other parts of the national research enterprise, and their ability to transfer new knowledge and ideas to those who productively use them in our society and economy. This report examines trends in university finance, prospects for improving university operations, opportunities for deploying technology, and improvement in the regulation of higher education institutions. It also explores ways to improve pathways to graduate education, take advantage of opportunities to increase student diversity, and realign doctoral education for the careers new doctorates will follow. Research Universities and the Future of America is an important resource for policy makers on the federal and state levels, university administrators, philanthropic organizations, faculty, technology transfer specialists, libraries, and researchers.

To Recruit and Advance: Women Students and Faculty in Science and Engineering - National Research Council (The National Academies Press, 2006)
Although more women than men participate in higher education in the United States, the same is not true when it comes to pursuing careers in science and engineering. To Recruit and Advance: Women Students and Faculty in Science and Engineering identifies and discusses better practices for recruitment, retention, and promotion for women scientists and engineers in academia. Seeking to move beyond yet another catalog of challenges facing the advancement of women in academic science and engineering, this book describes actions actually taken by universities to improve the situation for women. Serving as a guide, it examines the following: Recruitment of female undergraduates and graduate students. Ways of reducing attrition in science and engineering degree programs in the early undergraduate years. Improving retention rates of women at critical transition points2014from undergraduate to graduate student, from graduate student to postdoc, from postdoc to first faculty position. Recruitment of women for tenure-track positions. Increasing the tenure rate for women faculty. Increasing the number of women in administrative positions. This guide offers numerous solutions that may be of use to other universities and colleges and will be an essential resource for anyone interested in improving the position of women students, faculty, deans, provosts, and presidents in science and engineering.

Reaching Students: What Research Says About Effective Instruction in Undergraduate Science and Engineering - National Research Council (The National Academies Press, 2015)
The undergraduate years are a turning point in producing scientifically literate citizens and future scientists and engineers. Evidence from research about how students learn science and engineering shows that teaching strategies that motivate and engage students will improve their learning. So how do students best learn science and engineering? Are there ways of thinking that hinder or help their learning process? Which teaching strategies are most effective in developing their knowledge and skills? And how can practitioners apply these strategies to their own courses or suggest new approaches within their departments or institutions? Reaching Students strives to answer these questions. Reaching Students presents the best thinking to date on teaching and learning undergraduate science and engineering. Focusing on the disciplines of astronomy, biology, chemistry, engineering, geosciences, and physics, this book is an introduction to strategies to try in your classroom or institution. Concrete examples and case studies illustrate how experienced instructors and leaders have applied evidence-based approaches to address student needs, encouraged the use of effective techniques within a department or an institution, and addressed the challenges that arose along the way. The research-based strategies in Reaching Students can be adopted or adapted by instructors and leaders in all types of public or private higher education institutions. They are designed to work in introductory and upper-level courses, small and large classes, lectures and labs, and courses for majors and non-majors. And these approaches are feasible for practitioners of all experience levels who are open to incorporating ideas from research and reflecting on their teaching practices. This book is an essential resource for enriching instruction and better educating students.

Assessing and Responding to the Growth of Computer Science Undergraduate Enrollments - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
The field of computer science (CS) is currently experiencing a surge in undergraduate degree production and course enrollments, which is straining program resources at many institutions and causing concern among faculty and administrators about how best to respond to the rapidly growing demand. There is also significant interest about what this growth will mean for the future of CS programs, the role of computer science in academic institutions, the field as a whole, and U.S. society more broadly. Assessing and Responding to the Growth of Computer Science Undergraduate Enrollments seeks to provide a better understanding of the current trends in computing enrollments in the context of past trends. It examines drivers of the current enrollment surge, relationships between the surge and current and potential gains in diversity in the field, and the potential impacts of responses to the increased demand for computing in higher education, and it considers the likely effects of those responses on students, faculty, and institutions. This report provides recommendations for what institutions of higher education, government agencies, and the private sector can do to respond to the surge and plan for a strong and sustainable future for the field of CS in general, the health of the institutions of higher education, and the prosperity of the nation.

Graduate STEM Education for the 21st Century - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
The U.S. system of graduate education in science, technology, engineering, and mathematics (STEM) has served the nation and its science and engineering enterprise extremely well. Over the course of their education, graduate students become involved in advancing the frontiers of discovery, as well as in making significant contributions to the growth of the U.S. economy, its national security, and the health and well-being of its people. However, continuous, dramatic innovations in research methods and technologies, changes in the nature and availability of work, shifts in demographics, and expansions in the scope of occupations needing STEM expertise raise questions about how well the current STEM graduate education system is meeting the full array of 21st century needs. Indeed, recent surveys of employers and graduates and studies of graduate education suggest that many graduate programs do not adequately prepare students to translate their knowledge into impact in multiple careers. Graduate STEM Education for the 21st Century examines the current state of U.S. graduate STEM education. This report explores how the system might best respond to ongoing developments in the conduct of research on evidence-based teaching practices and in the needs and interests of its students and the broader society it seeks to serve. This will be an essential resource for the primary stakeholders in the U.S. STEM enterprise, including federal and state policymakers, public and private funders, institutions of higher education, their administrators and faculty, leaders in business and industry, and the students the system is intended to educate.

Sexual Harassment of Women: Climate, Culture, and Consequences in Academic Sciences, Engineering, and Medicine - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Over the last few decades, research, activity, and funding has been devoted to improving the recruitment, retention, and advancement of women in the fields of science, engineering, and medicine. In recent years the diversity of those participating in these fields, particularly the participation of women, has improved and there are significantly more women entering careers and studying science, engineering, and medicine than ever before. However, as women increasingly enter these fields they face biases and barriers and it is not surprising that sexual harassment is one of these barriers. Over thirty years the incidence of sexual harassment in different industries has held steady, yet now more women are in the workforce and in academia, and in the fields of science, engineering, and medicine (as students and faculty) and so more women are experiencing sexual harassment as they work and learn. Over the last several years, revelations of the sexual harassment experienced by women in the workplace and in academic settings have raised urgent questions about the specific impact of this discriminatory behavior on women and the extent to which it is limiting their careers. Sexual Harassment of Women explores the influence of sexual harassment in academia on the career advancement of women in the scientific, technical, and medical workforce. This report reviews the research on the extent to which women in the fields of science, engineering, and medicine are victimized by sexual harassment and examines the existing information on the extent to which sexual harassment in academia negatively impacts the recruitment, retention, and advancement of women pursuing scientific, engineering, technical, and medical careers. It also identifies and analyzes the policies, strategies and practices that have been the most successful in preventing and addressing sexual harassment in these settings.

Supporting Students' College Success: The Role of Assessment of Intrapersonal and Interpersonal Competencies - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
The importance of higher education has never been clearer. Educational attainment2014the number of years a person spends in school2014strongly predicts adult earnings, as well as health and civic engagement. Yet relative to other developed nations, educational attainment in the United States is lagging, with young Americans who heretofore led the world in completing postsecondary degrees now falling behind their global peers. As part of a broader national college completion agenda aimed at increasing college graduation rates, higher education researchers and policy makers are exploring the role of intrapersonal and interpersonal competencies in supporting student success. Supporting Students' College Success: The Role of Assessment of Intrapersonal and Interpersonal Competencies identifies 8 intrapersonal competencies (competencies involving self-management and positive self-evaluation) that can be developed through interventions and appear to be related to persistence and success in undergraduate education. The report calls for further research on the importance of these competencies for college success, reviews current assessments of them and establishes priorities for the use of current assessments, and outlines promising new approaches for improved assessments.

Barriers and Opportunities for 2-Year and 4-Year STEM Degrees: Systemic Change to Support Students' Diverse Pathways - National Academy of Engineering; National Academies of Sciences, Engineering,; Medicine
Nearly 40 percent of the students entering 2- and 4-year postsecondary institutions indicated their intention to major in science, technology, engineering, and mathematics (STEM) in 2012. But the barriers to students realizing their ambitions are reflected in the fact that about half of those with the intention to earn a STEM bachelor's degree and more than two-thirds intending to earn a STEM associate's degree fail to earn these degrees 4 to 6 years after their initial enrollment. Many of those who do obtain a degree take longer than the advertised length of the programs, thus raising the cost of their education. Are the STEM educational pathways any less efficient than for other fields of study? How might the losses be \

Undergraduate Research Experiences for STEM Students: Successes, Challenges, and Opportunities - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
Undergraduate research has a rich history, and many practicing researchers point to undergraduate research experiences (UREs) as crucial to their own career success. There are many ongoing efforts to improve undergraduate science, technology, engineering, and mathematics (STEM) education that focus on increasing the active engagement of students and decreasing traditional lecture-based teaching, and UREs have been proposed as a solution to these efforts and may be a key strategy for broadening participation in STEM. In light of the proposals questions have been asked about what is known about student participation in UREs, best practices in UREs design, and evidence of beneficial outcomes from UREs. Undergraduate Research Experiences for STEM Students provides a comprehensive overview of and insights about the current and rapidly evolving types of UREs, in an effort to improve understanding of the complexity of UREs in terms of their content, their surrounding context, the diversity of the student participants, and the opportunities for learning provided by a research experience. This study analyzes UREs by considering them as part of a learning system that is shaped by forces related to national policy, institutional leadership, and departmental culture, as well as by the interactions among faculty, other mentors, and students. The report provides a set of questions to be considered by those implementing UREs as well as an agenda for future research that can help answer questions about how UREs work and which aspects of the experiences are most powerful.

Beyond Bias and Barriers: Fulfilling the Potential of Women in Academic Science and Engineering - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2007)
The United States economy relies on the productivity, entrepreneurship, and creativity of its people. To maintain its scientific and engineering leadership amid increasing economic and educational globalization, the United States must aggressively pursue the innovative capacity of all its people&#8212women and men. However, women face barriers to success in every field of science and engineering; obstacles that deprive the country of an important source of talent. Without a transformation of academic institutions to tackle such barriers, the future vitality of the U.S. research base and economy are in jeopardy. Beyond Bias and Barriers explains that eliminating gender bias in academia requires immediate overarching reform, including decisive action by university administrators, professional societies, federal funding agencies and foundations, government agencies, and Congress. If implemented and coordinated across public, private, and government sectors, the recommended actions will help to improve workplace environments for all employees while strengthening the foundations of America&#39s competitiveness.

The Next Generation of Biomedical and Behavioral Sciences Researchers: Breaking Through - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Since the end of the Second World War, the United States has developed the world's preeminent system for biomedical research, one that has given rise to revolutionary medical advances as well as a dynamic and innovative business sector generating high-quality jobs and powering economic output and exports for the U.S. economy. However, there is a growing concern that the biomedical research enterprise is beset by several core challenges that undercut its vitality, promise, and productivity and that could diminish its critical role in the nation's health and innovation in the biomedical industry. Among the most salient of these challenges is the gulf between the burgeoning number of scientists qualified to participate in this system as academic researchers and the elusive opportunities to establish long-term research careers in academia. The patchwork of measures to address the challenges facing young scientists that has emerged over the years has allowed the U.S. biomedical enterprise to continue to make significant scientific and medical advances. These measures, however, have not resolved the structural vulnerabilities in the system, and in some cases come at a great opportunity cost for young scientists. These unresolved issues could diminish the nation's ability to recruit the best minds from all sectors of the U.S. population to careers in biomedical research and raise concerns about a system that may favor increasingly conservative research proposals over high-risk, innovative ideas. The Next Generation of Biomedical and Behavioral Sciences Researchers: Breaking Through evaluates the factors that influence transitions into independent research careers in the biomedical and behavioral sciences and offers recommendations to improve those transitions. These recommendations chart a path to a biomedical research enterprise that is competitive, rigorous, fair, dynamic, and can attract the best minds from across the country.

An American Crisis: The Growing Absence of Black Men in Medicine and Science: Proceedings of a Joint Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Black men are increasingly underrepresented in medical schools and in the medical profession. A diverse workforce is a key attribute of quality healthcare and research suggests that a diverse workforce may help to advance cultural competency and increase access to high-quality health care, especially for underserved populations. Conversely, lack of diversity in the health workforce threatens health care quality and access and contributes to health disparities. In this way, the growing absence of Black men in medicine is especially troubling, because their absence in medicine may have adverse consequences for health care access, quality, and outcomes among Black Americans and Americans overall. To better understand the factors that contribute to the low participation of Black men in the medical profession, facilitate discussion of current strategies used to increase their participation in medical education, and explore new strategies along the educational and professional pipeline that may have potential to increase participation in medicine, the National Academies of Sciences, Engineering, and Medicine and the Cobb Institute jointly convened a 2-day workshop in November 2017, in Washington, DC. This publication summarizes the presentations and discussions from the workshop.

Policy Implications of International Graduate Students and Postdoctoral Scholars in the United States - National Research Council (The National Academies Press, 2005)
Policy Implications of International Graduate Students and Postdoctoral Scholars in the United States explores the role and impact of students and scholars on US educational institutions and the US economy. The nation has drawn increasingly on human resources abroad for its science and engineering workforce. However, competition for talent has grown as other countries have expanded their research infrastructure and created more opportunities for international students. The report discusses trends in international student enrollments, stay rates, and examines the impact of visa policies on international mobility of the highly skilled.

Rising Above the Gathering Storm: Energizing and Employing America for a Brighter Economic Future - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2007)
In a world where advanced knowledge is widespread and low-cost labor is readily available, U.S. advantages in the marketplace and in science and technology have begun to erode. A comprehensive and coordinated federal effort is urgently needed to bolster U.S. competitiveness and pre-eminence in these areas. This congressionally requested report by a pre-eminent committee makes four recommendations along with 20 implementation actions that federal policy-makers should take to create high-quality jobs and focus new science and technology efforts on meeting the nation's needs, especially in the area of clean, affordable energy: 1) Increase America's talent pool by vastly improving K-12 mathematics and science education; 2) Sustain and strengthen the nation's commitment to long-term basic research; 3) Develop, recruit, and retain top students, scientists, and engineers from both the U.S. and abroad; and 4) Ensure that the United States is the premier place in the world for innovation. Some actions will involve changing existing laws, while others will require financial support that would come from reallocating existing budgets or increasing them. Rising Above the Gathering Storm will be of great interest to federal and state government agencies, educators and schools, public decision makers, research sponsors, regulatory analysts, and scholars.

Optimizing the Nation's Investment in Academic Research: A New Regulatory Framework for the 21st Century - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Research universities are critical contributors to our national research enterprise. They are the principal source of a world-class labor force and fundamental discoveries that enhance our lives and the lives of others around the world. These institutions help to create an educated citizenry capable of making informed and crucial choices as participants in a democratic society. However many are concerned that the unintended cumulative effect of federal regulations undercuts the productivity of the research enterprise and diminishes the return on the federal investment in research. Optimizing the Nation's Investment in Academic Research reviews the regulatory framework as it currently exists, considers specific regulations that have placed undue and often unanticipated burdens on the research enterprise, and reassesses the process by which these regulations are created, reviewed, and retired. This review is critical to strengthen the partnership between the federal government and research institutions, to maximize the creation of new knowledge and products, to provide for the effective training and education of the next generation of scholars and workers, and to optimize the return on the federal investment in research for the benefit of the American people.